PEMANFAATAN MULTIMEDIA UNTUK MENINGKATKAN HASIL BELAJAR KOMPETENSI DASAR TEKNOLOGI MENJAHIT - Kurniasih Kurniasih (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2018)
The purpose of this study is to determine theimprovement of students learning outcome, the factors thatsupport and inhibit the use of multi media. The research isclass action. It consists of two cycles, every cycle has four steps,they are: planning, action, observation and reflection. Thetechnique in analyzing the data is based on the qualitativeand quantitative data. The success indicator that is if thestudents pass 85%. The result of the research shows thatthere are improvement of students learning outcome onthe first cycle, the students have the average score, 75,5 and70% of mastery and on the second cycle, their average scoresbecome 81 and 85% of mastery. The factors that supportmulti media use are suitable to the students thought level,suitable to the purpose of the study, easy to create, while thefactor that inhibit is the limitation of space and time.